STRATEGI DRIVER GUIDE DALAM MENJAGA KELANGSUNGAN EKONOMI KELUARGA PADA MASA PANDEMI COVID-19 DI KUTA, BALI - Tanjung, Alfia; Punia, I Nengah; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 2 No 2 (2022): JISSOROT, 2022)
This study analyzes and describes the driver guide strategy and finds out the effectiveness of the strategy to maintain family economic continuity during the Covid-19 pandemic in Kuta, Bali. The approach used in this research is qualitative with descriptive explanatory type and analysis using rational choice theory from James Samuel Coleman emphasizes that an individual in carrying out an action will utilize the resources he has to achieve the desired goal. In this study, the driver guides utilized their available resources to achieve strategies in maintaining family economic continuity during the Covid-19 pandemic. The strategies carried out by the driver guides vary according to the resources they have, such as the savings they have to open a new business and loans from cooperatives or relatives. There are differences of opinion regarding the effectiveness of the strategies carried out by each driver guide based on the strategies carried out in maintaining family economic continuity during the Covid-19 pandemic. There are five crucial stages in the rational choice process, namely, determining priorities, weighing the available resources, selecting actors from the various available options, weighing the success or failure of the actions taken, and exchanging resources owned by other parties. The strategy carried out by the driver guides is also based on the five crucial stages, where the driver guides also determine priorities, consider the available resources, select actors from various available options, weigh the success or failure of the actions taken, and exchange resources owned by another party.   Keywords: Strategy, Driver Guide, Family Economy, Covid-19 Pandemic, Kuta, Bali